Two Area Preserving Maps from the Square to the p-Ball - Holhos, Adrian (Mathematical Modelling and Analysis, 2017)
We construct two area preserving maps from the square to the p-ball (the domain defined by |x|p + |y|p ≤ |a|p ) and use them to obtain low distorted uniform grids on the p-ball.